APLIKASI METODE ASSIGNMENT DALAM OPTIMASI PENANGANAN PERKARA HUKUM PADA KANTOR ADVOKAT: PENDEKATAN ANALISIS KUANTITATIF BERBASIS QM FOR WINDOWS - Dian Eka Matra Putra Bangun; Jhon Kristopel Manalu; Parapat Gultom (Kampus Akademik Publiser, 2026)
Operational management in law firms faces significant challenges in allocating limited time resources amidst high demand for case handling. This study aims to optimize the assignment of legal cases to advocates in order to minimize the total case completion time using the assignment method. The data consists of an estimated time matrix (in days) for four advocates handling four types of cases, namely Criminal Cases, Civil Cases, Industrial Relations Cases, and Intellectual Property Rights (IPR) Cases. Data analysis was conducted using QM for Windows (POM-QM) software. The optimization results show that systematic work distribution produces an efficient one-to-one allocation with a minimum total completion duration of 32 days. The implementation of this linear programming model is proven effective in assisting law firm management in making strategic decisions based on formal data.